2021
DOI: 10.1007/s10237-021-01496-8
|View full text |Cite
|
Sign up to set email alerts
|

A multiscale optimisation method for bone growth scaffolds based on triply periodic minimal surfaces

Abstract: Tissue engineered bone scaffolds are potential alternatives to bone allografts and autografts. Porous scaffolds based on triply periodic minimal surfaces (TPMS) are good candidates for tissue growth because they offer high surface-to-volume ratio, have tailorable stiffness, and can be easily fabricated by additive manufacturing. However, the range of TPMS scaffold types is extensive, and it is not yet clear which type provides the fastest cell or tissue growth while being sufficiently stiff to act as a bone gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 38 publications
0
15
0
1
Order By: Relevance
“…The first one defines the maximum 3D space dimension that can be accommodated within the smallest pore structure within the porous material as the pore size. Then it defines the maximum 2D plane dimension that interconnects the pore structure inside the porous material with other adjacent pore structures as the pore throat size, as shown in Figure 2A ( Afshar et al, 2016 ; Jette et al, 2018 ; Ambu and Morabito, 2019 ; Wang et al, 2020 ; Lehder et al, 2021 ; Timercan et al, 2021 ). The second one defines the maximum 2D plane dimension of the pore within the porous material that interconnects with other adjacent pore structures as the pore diameter.…”
Section: Definition Of Pore Structure Dimensionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first one defines the maximum 3D space dimension that can be accommodated within the smallest pore structure within the porous material as the pore size. Then it defines the maximum 2D plane dimension that interconnects the pore structure inside the porous material with other adjacent pore structures as the pore throat size, as shown in Figure 2A ( Afshar et al, 2016 ; Jette et al, 2018 ; Ambu and Morabito, 2019 ; Wang et al, 2020 ; Lehder et al, 2021 ; Timercan et al, 2021 ). The second one defines the maximum 2D plane dimension of the pore within the porous material that interconnects with other adjacent pore structures as the pore diameter.…”
Section: Definition Of Pore Structure Dimensionmentioning
confidence: 99%
“…The ability of these materials to promote bone tissue repair and reconstruction has been widely recognized ( Xia et al, 2023 ; Dall'Ava et al, 2020 ; Chen et al, 2018 ). The bioengineered porous bone tissue materials promote bone tissue reconstruction and repair by providing an effective support effect and maintaining a good mechanical environment at the defect site after implantation ( Ponader et al, 2010 ; Wang et al, 2020 ; Lehder et al, 2021 ). They also act as a scaffold for tissue growth, enabling the growth and formation of fibers, blood vessels, and bone tissue ( Harrison et al, 2014 ; Taniguchi et al, 2016 ; Wu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mehta et al [ 14 ] showed that the strain of about 1% in the early stage of bone healing is conducive to the growth of bone tissue. For the repair of load-bearing bone defects, the traditional method is to use porous scaffolds whose mechanical properties match the bone tissue for repair [ 15 ]. To achieve the strain window described above, scaffolds that are softer than bone tissue should be used at the site of bone defect.…”
Section: Introductionmentioning
confidence: 99%
“…As a pore-forming unit, TPMS can realize the digital representation of a porous structure. There are also advantages to the porous structures found in capillaries, such as diffusion of nutrients and small pore size limitations [ 15 ]. Davar Ali investigated the effect of TPMS scaffold structures on cell adhesion during the diffusion of nutrient delivery in culture media [ 16 ].…”
Section: Introductionmentioning
confidence: 99%